Synergistic Bioactive Ointment: ZnO Nanoparticles Combined with Carica papaya Latex and Aloe Vera Gel for Broad-Spectrum Biomedical Applications - Geethma Ekanayake; Amavin Mendis; Supuni Wijayawardana; Charitha Thambiliyagodage; Madara Jayanetti (PLoS ONE, 2026)
The development of multifunctional topical formulations that combine natural bioactives with therapeutic nanomaterials offers a promising route to improved wound healing and management. Carica papaya fruit latex powder and Aloe barbadensis Miller gel were incorporated as active ingredients into an ointment base consisting of ZnO nanoparticles, cassava starch, and white petroleum jelly to formulate a novel topical medication with enhanced biological properties. According to the 2,2-diphenyl-1-picrylhydrazyl antioxidant assay, IC 50 values of Carica papaya latex, Aloe gel, and ZnO nanoparticles were 454.54, 312.50, and 490.82 μg/mL, respectively. Carica papaya latex powder showed a protease activity of 58.40 units/mg of the solid. The ointment base exhibited the lowest blood clotting index (3.57 ± 6.09%), suggesting strong coagulation potential, whereas ZnO showed the highest (22.26 ± 1.09%), indicating minimal clotting ability under the current experimental setup. Erythrocyte adsorption was also highest in the ointment base (84.10 ± 1.09%), reinforcing its strong interaction with blood components. Cassava starch and petroleum jelly displayed moderate Red Blood Cell (RBC) attachment percentages. Platelet adhesion with the ointment base (61.55 ± 1.09%) and cassava starch (53.97 ± 2.40%) showed better platelet interaction than ZnO (29.1 ± 4.08%). Hemolysis data indicated that petroleum jelly caused the highest RBC lysis at all concentrations, while the ointment base showed the lowest activity, indicating better hemocompatibility. Clotting time analysis further highlighted the ointment base and petroleum jelly as effective pro-coagulants (13.30 s and 13.34 s, respectively), whereas ZnO (18.34 min) and cassava starch (48.34 s) exhibited delayed clotting. The ointment in which the base: active ingredient ratio is 7:3, and within, Carica papaya latex: Aloe gel ratio 1:4, shows the maximum antibacterial activity against Staphylococcus aureus and Escherichia coli . The MBC/MIC ratios of the above ointment for the two organisms were lower than 4, suggesting a bactericidal effect. The time-kill curves show a gradual reduction in bacterial survival over time, with the most significant reduction observed in the ointment with the highest proportion of Aloe vera.